APAKAH SENTIMEN LAPORAN TAHUNAN TERKAIT DENGAN KINERJA KEUANGAN? - Milardi Matius Thie Mailatu; Ari Budi Kristanto (Jurnal Akuntansi dan Pajak, 2023)
Management conveys various information about the company using images, numeric or textual disclosures. Numerical information has extensively used in accounting and financial analysis. Although textual data is voluminously available, it is still relatively rarely used to assess the firm condition. Textual information broadly disclosed through social media, annual reports, websites and press releases. This research will specifically focus on the phenomena gap of textual data utilization in accounting analysis. This study aims to see whether the company's financial performance correlates with the sentiment in the annual report. This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2016-2020 as research objects. Based on purposive sampling method, there are 102 companies (510 research observations) which were selected as the sample. Company performance is measured using the return on investment indicator. The sentiment of the annual report is analyzed using VADER method. This method generates positive and negative sentiment scores from the annual report based on the lexicon approach. The results show that financial financial performance is positively correlated with positive sentiment in the narrative of the annual report. Furthermore, financial performance is negatively correlated with negative sentiment in the annual report narrative.